SURG-09. SURGICAL AND PERI-OPERATIVE CONSIDERATIONS FOR BRAIN METASTASES: A NATIONWIDE ANALYSIS. (12th August 2019) - Gupta, Saksham; Larsen, Alexandra Giantini; Dawood, Hassan; Fandino, Luis; Knelson, Erik; Smith, Timothy; Lee, Eudocia; Aizer, Ayal; Bi, Wenya
Abstract: BACKGROUND: Brain metastases are the most frequent brain tumors in adults, whose management remains nuanced. We aim to improve risk stratification for brain metastases patients who might be candidates for surgical resection. METHODS: We conducted a nationwide, retrospective cohort analysis of adult patients who received craniotomy for resection of brain metastasis using the 2012–2015 American College of Surgeons National Surgical Quality Improvement Project databases. Our primary outcomes of interest were post-operative medical complications, reoperation, readmission, and mortality. RESULTS: 3500 cases were included, of which 17% were considered frail and 24% were infratentorial. The most common 30-day medical complications were pneumonia (4%), venous thromboembolism (VTE;3%), and urinary tract infections (2%). Cardiac events and cerebrovascular accidents tended to occur in the early post-operative period, while VTEs and infections occurred in a more delayed fashion. Reoperation and unplanned readmission occurred in 5% and 12% of patients, respectively. Infratentorial approach and frailty were associated with reoperation before discharge (OR 2.0 for both; p=0.01 and p=0.03 respectively), but not after discharge. Frail patients were especially at risk for surgical evacuation of hematoma (OR 3.6). Infratentorial approaches conferred heightened risk for readmission for hydrocephalus (OR 5.1, p=0.02) and reoperation for cerebrospinal fluid diversion (OR 7.1, p< 0.001). Overall 30-day mortality was 4%, with nearly three-quarters occurring after discharge. Pre-frailty and frailty were associated with increased odds for post-discharge mortality (OR 1.7 and 2.7, p< 0.05), but not pre-discharge mortality. We developed a model to predictors of death, which identified frailty, thrombocytopenia, and high American Society of Anesthesiologists score as the strongest predictors of 30-day mortality (AUROC 0.75). CONCLUSION: Optimization of metrics contributing to patient frailty and heightened surveillance in patients with infratentorial metastases may be considered in the peri-operative period.